A SORROW SHARED IS A SORROW HALVED—AGE DIFFERENCES IN EXTRINSIC EMOTION REGULATION - Kunzmann, U. (Innov Aging, 2017)
Previous work suggests age-related improvement in emotion regulation. Although emotion regulation is embedded in social contexts, the majority of studies has adopted an individual approach examining how well individuals regulate their own emotions. Extending this work, the goal of this study was to test age differences in the ability to regulate one’s partner’s emotions. In each trial, one partner relived negative emotions associated with an acute personal problem, while the other engaged in a control task. Subsequently the couple came together and talked about the problem. Immediately after each conversation, both partners rated the conversation according to multiple respects (e.g., quality and satisfaction with the conversation, success of regulatory attempts). Preliminary analyses using actor-partner-interdependence models revealed that older couples were more successful at down-regulating each other’s negative emotions. They further reported higher agreement on regulatory efforts and success. Implications for research on socio-emotional aging and social competence are  discussed.